URGENSI PROFESIONALISME GURU DALAM PENDIDIKAN - Alimin, Alimin; Maghfur, Moh.; Hakim, Lutfi; Nur Khofifah, Sinta; Berti Ibmagara, Afridha (Jurnal Ilmu Pendidikan Islam, 2024)
Education is the main foundation of a nation's development, and the role of teachers is the core in producing a quality generation. The teaching profession is not only limited to transferring knowledge, but also shaping students' characters, attitudes, and skills. This research uses a literature study method with a qualitative approach to explore the urgency of teacher professionalism in education. The results show that the teaching profession requires professional, pedagogical, social, and personality competencies, as stipulated in Law No.14 of 2005. In addition, the implementation of a professional code of ethics is important to maintain integrity and ethics in relationships with students, colleagues and the community. These competencies and codes of conduct support teachers in carrying out their roles effectively, contributing positively to the formation of students' character and skills, and creating a safe and supportive learning environment. Thus, understanding and applying teacher competencies and codes of conduct are key to improving the quality of education and making a positive contribution to the nation's progress.